2017
DOI: 10.1007/s11095-017-2160-0
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Transport Activity and Trafficking of MRP2/ABCC2 Polymorphic Variants

Abstract: Purpose Multidrug resistance-associated protein 2 (MRP2/ABCC2) is an efflux pump that removes drugs and chemicals from cells. We sought to characterize the expression, trafficking and in vitro activity of seven single nucleotide polymorphisms (SNPs) in the ABCC2 gene. Methods ABCC2 SNPs were generated using site-directed mutagenesis and stably expressed in Flp-In HEK293 cells, which allows targeted insertion of transgenes within the genome. Total and cell surface expression of MRP2 as well as accumulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…ABCC2 transporter is crucial for glutathione, glucuronide and sulfate conjugates of many drugs, thus it mediates their intracellular concentration. Variant p.Val417Ile (rs2273697) has been shown in in vitro models to decrease the apparent affinity for substrates conjugated with glutathione and glucuronide, and to decrease the transport activity [ 105 , 106 ]. Opposite findings came from the work of Haenisch and colleagues on bioavailability of talinolol, who reported that p.Val417Ile variant was associated with higher activity of intestinal ABCC2 [ 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…ABCC2 transporter is crucial for glutathione, glucuronide and sulfate conjugates of many drugs, thus it mediates their intracellular concentration. Variant p.Val417Ile (rs2273697) has been shown in in vitro models to decrease the apparent affinity for substrates conjugated with glutathione and glucuronide, and to decrease the transport activity [ 105 , 106 ]. Opposite findings came from the work of Haenisch and colleagues on bioavailability of talinolol, who reported that p.Val417Ile variant was associated with higher activity of intestinal ABCC2 [ 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the p.G693R mutation was observed in 2 out of 7 patients, indicating that the p.G693R mutation might be a potential hotspot mutation in Chinese DJS patients. ABCC2 p.G693R is a missense mutation located in the first ATP-binding domain of MRP2 protein [17]. We demonstrated that while wild-type MRP2 predominantly localized to the cell surface and cytoplasm, the MRP2 p.G693R mutant was predominantly retained in the cytoplasm rather than the cell surface.…”
Section: Discussionmentioning
confidence: 86%
“…In the present study, the p.G693R mutation was observed in 2 out of 7 patients, indicating that the p.G693R mutation might be a potential hotspot mutation in Chinese DJS patients. ABCC2 p.G693R is a missense mutation located in the first ATP-binding domain of MRP2 protein [25]. We demonstrated that while wild-type MRP2 predominantly localized to the cell surface and cytoplasm, the MRP2 p.G693R mutant was predominantly retained in the cytoplasm rather than the cell surface.…”
Section: Djs Is Characterized By Predominantly Conjugated Hyperbilirumentioning
confidence: 86%